NOVEL XRCC4 MUTATIONS IN AN INFANT WITH MICROCEPHALIC PRIMORDIAL DWARFISM, DILATED CARDIOMYOPATHY, SUBCLINICAL HYPOTHYROIDISM, AND EARLY DEATH: EXPANDING THE PHENOTYPE OF XRCC4 MUTATIONS - Fredette, Meghan E. (AACE Clin Case Rep, 2019)
OBJECTIVE: Microcephalic primordial dwarfism (MPD) is a group of clinically and genetically heterogeneous disorders which result in severe prenatal and postnatal growth failure. X-ray repair cross-complementing protein 4 (XRCC4) is a causative gene for an autosomal recessive form of MPD. The objective of this report is to describe novel XRCC4 mutations in a female infant with MPD, dilated cardiomyopathy, and subclinical hypothyroidism. METHODS: Genetic testing was performed using a comprehensive next generation sequencing panel for MPD, followed by targeted XRCC4 gene sequencing. RESULTS: We report the case of a 970-gram, 35-cm, female infant (weight z score −5.05, length z score −4.71) born at 36 weeks and 3 days gestation. Physical examination revealed triangular facies, micrognathism, clinodactyly, and second and third toe syndactyly. Initial echocardiogram at birth was normal. Follow-up echocardiogram at 60 days of life revealed dilated cardiomyopathy with moderate left ventricular systolic dysfunction (ejection fraction was 40 to 45%), and anticongestive therapy was initiated. Thyroid testing revealed subclinical hypothyroidism with elevated thyroid-stimulating hormone of 13.0 μIU/mL (reference range is 0.3 to 5.0 μIU/mL) and normal free thyroxine by dialysis of 1.6 ng/dL (reference range is 0.8 to 2.0 ng/dL). Levothyroxine was initiated. Postnatal growth remained poor (weight z score at 3 months −4.93, length z score at 3 months −6.48), including progressive microcephaly (head circumference z score at 3 months −10.94). Genetic testing revealed novel compound heterozygous XRCC4 variants in trans: c.628A>T and c.638+3A>G. The child ultimately had cardiopulmonary arrest and died at 6 months of life. CONCLUSION: Molecular diagnosis in MPD is key to defining the natural history, management, and prognosis for patients with these rare disorders.